(3QSGdI aj JhVjM CMhGd GdLHGd hGdLgGJ hGdHMGQ hGdadhGJs ((3ESeGYjd Hf eMeO s)
(3ChdgG (B:s
(3hgPg QSGdI dWjaI cGdTQM ai JhVjM eG ai gPg GdOGFQI JHjf ddfGXQ ajgG CMhGd GdLHGd hGdLgGJ hGdHMGQ hGdadhGJ heG ETJedJ Ydjg ef GdegGdc s
(3BNQgG (B:s
(3hGdghd GdYXje GdebYO Gdebje EeG HOGQ GdfYje hGdQVhGf hEeG HOGQ GdLMje hGdfjQGf hPdc HeG TGA GdMfGf GdefGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs